2005
DOI: 10.1111/j.0001-6349.2005.00729.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of placental removal method and site of uterine repair on postcesarean endometritis and operative blood loss

Abstract: Manual removal of the placenta at cesarean delivery results in more operative blood loss and a higher incidence of postcesarean endometritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Many studies investigated the rate of postoperative fever in different uterine repair groups, and most of the results revealed no significant differences among them [21,34,38,47,49,51]. Likewise, the incidences of endometritis and wound infection following cesarean delivery were similar in the two groups of exteriorized and in situ uterine repair techniques [17,[34][35][36][37]44,47]. Batsu et al [35] reported that manual removal of the placenta during cesarean surgeries is a major risk factor for endometritis.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies investigated the rate of postoperative fever in different uterine repair groups, and most of the results revealed no significant differences among them [21,34,38,47,49,51]. Likewise, the incidences of endometritis and wound infection following cesarean delivery were similar in the two groups of exteriorized and in situ uterine repair techniques [17,[34][35][36][37]44,47]. Batsu et al [35] reported that manual removal of the placenta during cesarean surgeries is a major risk factor for endometritis.…”
Section: Postoperative Complicationsmentioning
confidence: 99%
“…Similar results were noted in another study by Ezechi et al (742 mL vs. 872 mL) [ 34 ]. Moreover, the mean postoperative drop in hemoglobin level differed in several studies, ranging from 1–1.4 g/dL in the exteriorized uterine repair group and 1.2–1.7 g/dL in the in situ (non-exteriorization) repair group [ 35 , 36 , 37 , 38 ]. Despite significant differences in estimated blood loss and the postoperative drop in hemoglobin level, the percentage of blood transfusions after cesarean delivery between the two uterine repair techniques did not differ in previous studies [ 17 , 33 , 34 , 36 , 37 , 38 , 39 ].…”
Section: Surgical Techniques and Assistive Devices Used In Cesareamentioning
confidence: 99%
“…Ces résultats ne semblent pas avoir diffusé puisqu'une large majorité des maternités de l'échantillon étudié (84 %) recommandaient toujours la déli-vrance manuelle lors d'une césarienne. Depuis 2003, date de réalisation de notre enquête, d'autres essais randomisés sont venus confirmer ces résultats antérieurs [5,7,10]. Dans les recommandations élaborées par le CNGOF en 2004, la délivrance manuelle immédiate est déconseillée [20].…”
Section: Prise En Charge Du Placenta Lors D'une Césarienneunclassified
“…Ce constat d'une inadéqua-tion des soins dans des séries d'HPP, mortelles ou non, amène une question : s'agit-il d'une sélection de cas où la pratique individuelle s'est écartée de la politique locale de soins relative aux HPP, ou d'une inadéquation de la politique de soins relative aux HPP au niveau de la maternité ? L'analyse des données de la littérature montre que certaines interventions ont une influence sur l'incidence et/ou la gravité de l'HPP, en particulier en termes de prévention [5][6][7][8][9][10][11][12][13][14][15][16][17]. Il paraît donc important de savoir quelle est la traduction de ces résultats acquis dans les politiques de soins des maternités.…”
Section: Introductionunclassified
“…[25][26][27] Sharp incision at the time of cesarean section, as compared to blunt expansion, increases the incidence of postpartum hemorrhage (13% vs. 9%) and need for a transfusion (2% vs 0.4%). [25][26][27] Sharp incision at the time of cesarean section, as compared to blunt expansion, increases the incidence of postpartum hemorrhage (13% vs. 9%) and need for a transfusion (2% vs 0.4%).…”
Section: Primary Preventionmentioning
confidence: 99%